Extracting risk aversion estimates from option prices/implied volatility - Pillay, Aveshen (Division of Actuarial Science, 2015)
The risk neutral density function is the distribution implied by the market price of derivative securities, namely options. It encloses the assumption that arbi-trage free conditions persist in the market. Given the historical evolution of stock prices, an investor will form some belief about the future progression of the stock price.